2022
DOI: 10.7759/cureus.29623
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Risk Factors of Delayed Speech and Language in Children: A Cross-Sectional Study

Abstract: IntroductionCommunication is the exchange of information through speaking, writing, and other mediums. Speech is the expression of thoughts in spoken words. Language is the principal method that humans use for relaying information; consisting of words conveyed by speech, writing, or gestures. Language is the conceptual processing of communication. Problems in communication or oral motor function are called speech and language disorders. Developmental delay is diagnosed when a child does not attain normal devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…For example, the concept of speech delay may be interpreted differently in Saudi Arabia than in other countries. Additionally, the lower prevalence may be due to a difference in the prevalence of risk factors for speech delay in Saudi Arabia compared to other countries [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the concept of speech delay may be interpreted differently in Saudi Arabia than in other countries. Additionally, the lower prevalence may be due to a difference in the prevalence of risk factors for speech delay in Saudi Arabia compared to other countries [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous studies that have shown an association between parental education level and speech delay [ 16 ]. Lower parental education level is related to lower socioeconomic status, which in turn is associated with an increased risk of speech delay [ 13 ]. Lower socioeconomic status may be related to factors such as limited access to early intervention services, increased stress levels, and exposure to environmental toxins [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with obstructive sleep apnea-hypopnea syndrome have a higher incidence rate of malocclusion and lower score of cognitive function than the healthy control ( Cai et al, 2013 ); those with chronic mouth breathing develop malocclusion that changes the shape of their face and mouth, and their cognitive and academic abilities decline as compared to the nasal breathing control group ( Kuroishi et al, 2015 ; Grippaudo et al, 2016 ). Thumb/digit sucking habits raise a child’s risk of increased overjet and open bite followed by malocclusion and speech and language delay ( Ling et al, 2018 ; Kumar et al, 2022 ). In this way, malocclusion-induced cognitive dysfunction is considered to be a serious health hazard not only to the elderly but also the young.…”
Section: Introductionmentioning
confidence: 99%
“…Early identification and intervention can prevent language delay from interfering with formal education and behavioral adjustment (5). There have been numerous studies conducted to identify risk factors, predictors, and prevalence of language disorders in children (3,(6)(7)(8)(9)(10). Additionally, there is a considerable body of research focused on interventions for children with language delay (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%